2012
DOI: 10.17578/16-3/4-1
|View full text |Cite
|
Sign up to set email alerts
|

Return-based Style Analysis in Australian Funds

Abstract: This study applies return-based style analysis to a sample of Australian managed and superannuation funds, seeking to compare their asset allocation strategies across different style groups. Style analysis is performed using a rolling window estimation technique. As expected, riskier fund classes are more exposed to the riskier benchmarks. Further, differences in institutional and legal settings lead the managers of managed and superannuation funds to invest differently, with the latter employing a more conser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(27 reference statements)
1
3
0
Order By: Relevance
“…Then there will be transaction exposures in the company and face the risk of exchange rate fluctuations, so companies that have a large size will be more likely to do risk management without hedging to protect their companies In hypothesis four (4), namely cash flow which has a negative and significant effect on the use of derivative instruments as hedging decision making "is proven. The results of this study have confirmed research conducted by Ahmad [10], Paranita [34] and Nguyen and Faff [8] that cash flow has a negative effect on hedging. The results of this study indicate that the higher the company's cash flow will further reduce the possibility of the company to hedge because of the company's adequate cash flow conditions.…”
Section: Conclutionsupporting
confidence: 90%
See 2 more Smart Citations
“…Then there will be transaction exposures in the company and face the risk of exchange rate fluctuations, so companies that have a large size will be more likely to do risk management without hedging to protect their companies In hypothesis four (4), namely cash flow which has a negative and significant effect on the use of derivative instruments as hedging decision making "is proven. The results of this study have confirmed research conducted by Ahmad [10], Paranita [34] and Nguyen and Faff [8] that cash flow has a negative effect on hedging. The results of this study indicate that the higher the company's cash flow will further reduce the possibility of the company to hedge because of the company's adequate cash flow conditions.…”
Section: Conclutionsupporting
confidence: 90%
“…This result is supported by Andison's research [4], his research on manufacturing companies in the 2013-2015 period listed on the Indonesia Stock Exchange, proves that liquidity has a negative and significant effect on hedging. Whereas research conducted by Putro [3]; Nguyen and Faff [8], results that liquidity has a positive effect on hedging decisions.…”
Section: Companiesmentioning
confidence: 85%
See 1 more Smart Citation
“…Underperforming funds may therefore take more risks to bet on better performance given the disproportionate response from cash flows to previous fund performance. Underperforming funds may also alter the level of portfolio risk before the reporting date to manipulate their performance record Goetzmann et al, 2007;Lakonishok et al, 1991), or to conduct asset allocation strategies to promote certain investment style (Faff et al, 2012). On the other hand, funds may use risk shifting to indicate active trading or superior stock selection ability, which may not necessarily indent investors' benefits Kacperczyk et al (2005).…”
Section: Introductionmentioning
confidence: 99%